Implementation of a Realistic Mathematics Education to Improve Junior High School Students' Creative Thinking - Saleh, Hairus; Trisanti, Yuliana (SAINTIS Publishing, 2024)
Based on observation results, students' low level of creative thinking in mathematics lessons is influenced by the use of inappropriate methods, so teachers are required to innovate using fun learning methods. One method that makes students interested in learning mathematics is a realistic mathematics learning method. This research aims to improve students' creative thinking abilities in positive whole number material using a Realistic Mathematics Learning approach. Based on the research results, it was found that students' creative thinking increased from 25.94% to 66.7% in the first cycle, and 80.96% in the second cycle. After conducting research on the Realistic Mathematics Education (RME) approach to improve students' creative thinking, it can be seen from the results of initial observations that there has been quite a significant increase until the second cycle process.